Proposal of New Activation Function in Deep Image Prior. Issue 8 (17th June 2020) - Segawa, Ryo; Hayashi, Hitoshi; Fujii, Shohei
Abstract : We propose a new activation function and verify its performance in a deep image prior network. The new activation function is RSwish, which is Swish with a random slope for x  < 0 assuming that the input value of the activation function is x . In addition, we manipulate the probability of the random number and observe the effect. As a result, we found that RSwish can perform better than Swish by manipulating probabilities according to the degree of color change in the image. © 2020 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.